International Environmental Standards Handbook - Olson, Scott (CRC Press, 2009)
The International Environmental Standards Handbook provides the necessary historical background to understand the current status of international environmental standards. The practicality of the book is evident in the inclusion of material: copies of available treaties, laws and standards, as well as recommendations for businesses.